Analysis of the Use of CAPM in Investing Decisions in the Financial Sector Listed on the IDX for the Period 2020 – 2022 - Marcella Trianita Abur; Salija Ridayati; Rr Jihan Faadhilah Yuwandono; Maria Yovita R. Pandin (Finance : International Journal of Management Finance, 2023)
This study aims to analyze the use of the Capital Asset Pricing Model (CAPM) in making investment decisions in the financial sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. This research method involves collecting historical stock price data and financial data of companies listed in the IDX financial sector during the period under study. This research uses a descriptive research design with a quantitative approach and uses secondary data. Furthermore, statistical analysis will be conducted to test the effect of using CAPM on investment decisions. The results of this study are expected to provide valuable insights for investors and financial market participants. This research can also help in identifying companies in the financial sector that have higher return potential based on CAPM-based analysis.